Defect‐Rich CoP/Nitrogen‐Doped Carbon Composites Derived from a Metal–Organic Framework: High‐Performance Electrocatalysts for the Hydrogen Evolution Reaction. Issue 13 (16th June 2015) - Zhang, Zhe; Hao, Jinhui; Yang, Wenshu; Tang, Jilin
Abstract A defect‐rich CoP/nitrogen‐doped carbon composite is reported for the first time derived from ZIF‐67 by means of low‐temperature phosphidation process. As a hydrogen evolution reaction electrocatalyst, the obtained CoP‐N‐C has high HER activity and good stability with a low onset overpotential of 31 mV, a small Tafel slope of 42 mV dec−1, a large exchange current density of 1.6×10−1 mA cm−2, and a 10 mA cm−2 current density at overpotential 91 mV.